Stratigraphy Seismic and sedimentation Development of Middle Baong Sand, Aru Field, North Sumatera Basin - Natasia, Nanda; Syafri, Ildrem; Alfadli, Muhammad Kurniawan; Arfiansyah, Kurnia (UIR PRESS, 2016)
This paper defines the stratigraphic sequence focused on Middle Baong Sand. The analyses aim to understand the sedimentation pattern regarding to sequence stratigraphy model including its lateral and vertical succession based on seismic and well data. The study can be used in ranking the prospect for new oil field. Based on the analyses in 39 seismic sections and 2 wireline log, the area are consist of three depositional sequences, namely sequence I (consist of HST I) Sequence II (consist of TST II and LST II), and Sequence III (consist of TST III).  Baong Formation are deposited when the sea level are rising regionally at Middle Miocene (N7-N15) makes the sediment deposited in deep water environment. while Middle Baong Sand are deposited in the minor falling stage placed at N13 (Middle of Middle Miocene). In this episode, there is a change in depositional setting from bathyal to middle neritic. Clastic origin of this deposits were interpreted came from South-South West direction or from Bukit Barisan where at that time is started to uplift.